(3cJGH GdNWs - (3CHhHcQ eMeO Hf GdSQj Hf Sgd GdeYQha HGHf GdSQGL,J (B316 (3g` s
(3ChdgG (B:s
(3bGd CHh HcQ GdcJGH OGd Ydi GdcdGe , ceG Cf GdcdGe OGd Ydi eG ai GdfaS s
(3BNQgG (B:s
(3bO PcQfGLejY eG YQV ai GdNW hGSJbUjfGg LgOfG hCVafG Edi Pdc eG PcQg GdfGS ai cJH GdgLGA GbJOGA Hge hEf de jcf ef Yde GdNW ai TF Je cJGH GdNW s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B136s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs